Social Sustainability in Systematic Literature Review in Software Engineering - Silva, Anderson Yoshiaki Iwazaki da (2024)
Systematic Literature Reviews (SLR) have been widely used by the Software Engineering (SE) academic community to synthesize evidence and identify research trends and gaps in various research topics. At the same time, SLR have also aimed to support decision-making in the SE industry; however, one of the major challenges is still to provide truly relevant, applicable SLR results to industry practitioners. Moreover, it is still missing an understanding of who the involved with SLR and/or stakeholders are exactly. Objective: The main goal of this PhD thesis is to introduce the concept of social sustainability in SLR, particularly considering those reviews in the SE context. In the SLR context, social sustainability emphasizes generating knowledge that remains valuable and applicable to future stakeholders. For this, a specific goal was to propose a process named ipSLR to conduct SLR whose results are relevant and useful to the SE industry. Method: The research was based on four steps. The first step identified and mapped the needs and roles of stakeholders in SLR, resulting in a stakeholder model for SLR. The second step analyzed the relevance of including a subject of SLR in graduate courses, exploring the benefits and challenges of SLR for students and providing insights of what should be considered when new researchers (i.e., students) conduct SLR. The third step identified the benefits of counting on an SLR specialist during the SLR process. Finally, the fourth step proposed ipSLR, which focuses on conducting relevant and useful SLR to the SE industry. To validate this new process, we surveyed industry professionals to identify its adequacy. Results: This PhD thesis resulted in the inclusion of the concept of social sustainability in SLR, aiming to improve the relevance and usefulness of SLR for the SE industry and strengthen the collaboration between academia and industry. Conclusion: Conducting socially sustainable SLR can be considered a change in the mindset of how to deal with SLR that, ultimately, could lead to SLR relevant to the SE community, particularly industry practitioners.